If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + x * x * x + -9x * x = 0 Multiply x * x 20x + x2 * x + -9x * x = 0 Multiply x2 * x 20x + x3 + -9x * x = 0 Multiply x * x 20x + x3 + -9x2 = 0 Reorder the terms: 20x + -9x2 + x3 = 0 Solving 20x + -9x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(20 + -9x + x2) = 0 Factor a trinomial. x((4 + -1x)(5 + -1x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Subproblem 3
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {0, 4, 5}
| (5x+6)+(-6x+5)= | | 20x+x*x*x+9x*x=0 | | 32x+7=15 | | 7+x+(4x+7)= | | 2x+4=16-x | | 4w=-1 | | 5x=6y | | 2x+3=147 | | 9x^4+4x^2+1=0 | | 10x^2-4X+12=Y | | 34-5x=4x+24 | | x^2-4x=2 | | x^2-605x+1206=0 | | 8-7x=98-42x | | 2x+3-4=3x+6+6 | | x^10*e^6= | | -9x^3+18x^2-12x-8= | | 2*x*x-8=42 | | 2*x=40 | | 21=v(v-4) | | 2xx-8=40 | | 3x^2+7x+13=11 | | 2x-3=64 | | y-.8y=74 | | -5+12=17x-3-16x | | -5x*-3+8= | | 7x+1=-20 | | -5x*3+8= | | -3(x+8)-43=2-42 | | solvex^2=-7x-7 | | 22-x=2x+10 | | 22-x=2(x-5) |